Pengaruh Intellectual Capital, Likuiditas, Dan Solvabilitas Terhadap Kinerja Keuangan Perusahaan Infrastruktur Yang Terdaftar Di Bei Periode 2019-2023 - Nazhira Syarafina, Cynthia; Mira Munira; Ameilia Damayanti (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
The company's financial performance is an important thing that shows how the company can manage the effectiveness and efficiency of its resources, especially in infrastructure companies. Measuring a company's financial performance is generally done using liquidity ratios and solvency ratios which prove the company's ability to meet its long-term and short-term obligations. Intellectual capital can also be a measure of financial performance. This study has the aim of testing the significant influence of intellectual capital, liquidity, and solvency on the financial performance of infrastructure companies listed on the IDX for the 2019-2023 period. This study uses a quantitative method, with an associative approach to testing using multiple linear regression analysis. The results of the study indicate that intellectual capital and liquidity have a significant effect on the financial performance of infrastructure companies and solvency does not have a significant effect on the financial performance of infrastructure companies.